Report of the Working Group on District Planning Volume II - Planning Commission (Planning Commission, 1985)
It is the general experience that the planning per process at the State level is determined by many factors in addition to the constitutional division of unions between different tiers of authority. While the powers to formulate and implement plans broadly follow such a division of functions, the availability of resources, tire pattern of distribution of resources and any ether special administrative arrangement which may exist, tend to modify the planning process in varying measures.
Government of India Planning Commission
Government of India Planning Commission